Síntese, caracterização físico química e avaliação citotóxica de chalconas, chalconas sulfonamidas e quinolinonas - Castro, Mirian Rita Carrilho de (2017)
The chalcones are key intermediates for the biosynthesis of flavonoids and have shown an abundance of pharmacological effects including the antitumor effect. Thus, the synthesis and characterization of several chalcones and derivatives become important to develop a new class of compounds having antitumor activity. In the present work, the synthesis of chalcones, nitrochalcone sulfonamides and quinolinones was performed. By adjusting the reaction time and the sequence of the reactions, hybrids of open-chain chalcone sulfonamide whose molecular hybridization occurred at the ortho position of the benzoyl chalcone group through the Claisen- Schmidt condensation of acetophenone sulfonamide and nitrobenzaldehyde can be obtained at shorter reaction times, whereas quinolinone from cyclization at β carbon can be achieved if the reaction is stopped sequentially later. It is also noted that a novel structure, a chalcone (bis) sulfonamide, was prepared when chalcone was first synthesized and then reacted with benzenesulfonyl chloride. From the sulfonamide chalcones prepared with the m- aminoacetophenone sulfonamide and the o-, m- and p-nitrobenzaldehyde, a single product was formed. Among the 21 compounds prepared, five were ketone sulfonamides and sixteen were hybrid compounds (chalcones, chalcones, sulfonamides and quinolinones), which were purified by extraction, recrystallization and column chromatography and characterized by small molecule crystallography, melting point, Proton Nuclear Magnetic Resonance ( 1 H NMR) and infrared IV (IR). The antitumor activity was evaluated against three cancer cell lines: SF-295 (human glioblastoma), PC-3 (prostate) and HCT-116 (colon). Compounds 39, 40, 42, 43, 45a, 48a, 48b, 48c, 49 and 51 were cytotoxic to the three tumor cell lines tested. However, the quinolinones showed no relevant cytotoxic effect. It is also worth noting that compound 45a with a higher cytotoxic effect than doxorubicin, a drug used today against the three cancer cell lines evaluated, was a promising prototype for a new drug.